EXTH-14. INHIBITION OF THE ANGIOTENSIN II TYPE 2 RECEPTOR AT2R IS A NOVEL THERAPEUTIC STRATEGY FOR GLIOBLASTOMA. (14th November 2022) - Perryman, Richard; Renziehausen, Alexander; Shaye, Hamidreza; Kostagianni, Androniki; Tsiailanis, Antonis; Thorne, Tom; Chatziathanasiadou, Maria; Sivolapenko, Gregory; El Mubarak, Mohamed Ahmed; Han, Gye Won; Zarzycka, Barbara; Katritch, Vsevolod; et al.
Abstract: Glioblastoma (GBM) is a primary malignant brain tumor with poor clinical outcomes. Standard of care consists of surgical debulking followed by radiation and temozolomide, but the tumor invariably recurs, and median survival is only 18 months. Repurposing drugs used for the treatment of other diseases is a promising avenue to identify novel treatments for this highly aggressive form of cancer. One such class of compounds is angiotensin II (AngII) receptor blockers, commonly used to control blood pressure. We show that 80% of primary human GBM express the angiotensin II type 2 receptor (AT2R). In the presence of AngII, inhibition of AT2R using either PD123319 or EMA401 significantly inhibits GBM proliferation. This effect was lost in GBM cells with CRISPR/Cas9 mediated knockdown of AT2R. EMA401 inhibited invasion, angiogenesis, reduced GBM spheroid growth and induced apoptosis through caspase 3/7 activation. Furthermore, EMA401 induced changes in a number of growth regulatory pathways including apoptosis, DNA replication and focal adhesion. The crystal structure of AT2R bound to EMA401 revealed the receptor to be in an active-like conformation with helix-VIII blocking G protein or β-arrestin recruitment. We demonstrate that the architecture and interaction of EMA401 with AT2R differs drastically from complexes of AT2R with other compounds. Conjugation of EMA401 to angiopep-2 enhanced its blood brain barrier passage and reduced tumor volume in an orthotopic xenograft model of GBM. Targeting AT2R is a novel therapeutic strategy to treat GBM that should be explored in patients.